PELATIHAN DESAIN GRAFIS CORELDRAW SEBAGAI UPAYA PENGEMBANGAN SOFTSKILL SISWA SMP IBRAHIMY 3 SUKOREJO - Alfi Khairunnisa; Risqiatus Syarifah; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effectiveness of graphic design training using CorelDraw software in developing students’ soft skills at SMP Ibrahimy 3 Sukorejo. Softskills such as creativity, visual communication, collaboration, and problem-solving are essential competencies that should be cultivated from an early age, especially in the digital and creative industry era. The research employed a descriptive qualitative method with a participatory approach through direct observation, interviews, and documentation during the training sessions. The results indicate that the training not only enhanced students’ understanding of basic graphic design techniques but also fostered self-confidence, teamwork abilities, and an appreciation of visual aesthetics. Students’ active participation in designing logos, brochures, and other promotional media served as a key indicator of the success of this contextual learning approach. Therefore, the CorelDraw training has proven to be an effective strategy for strengthening students’ soft skills and is relevant to be integrated into 21st-century skills-based educational programs.